Crystal plane-dependent gas-sensing properties of zinc oxide nanostructures: experimental and theoretical studies - Yusuf V. Kaneti; Zhengjie Zhang; Jeffrey Yue; Quadir, Md Zakaria; Chuyang Chen; Xuchuan Jiang; Aibing Yu (R S C Publications, 2014)
The sensitivity of a metal oxide gas sensor is strongly dependent on the nature of the crystal surface exposed to the gas species. In this study, two types of zinc oxide (ZnO) nanostructures: nanoplates and nanorods with exposed (0001) and (10[1 with combining macron]0) crystal surfaces, respectively, were synthesized through facile solvothermal methods. The gas-sensing results show that sensitivity of the ZnO nanoplates toward ethanol is two times higher than that of the ZnO nanorods, at an optimum operating temperature of 300 °C. This could be attributed to the higher surface area and the exposed (0001) crystal surfaces. DFT (Density Functional Theory) simulations were carried out to study the adsorption of ethanol on the ZnO crystal planes such as (0001), (10[1 with combining macron]0), and (11[2 with combining macron]0) with adsorbed O− ions. The results reveal that the exposed (0001) planes of the ZnO nanoplates promote better ethanol adsorption by interacting with the surface oxygen p (O2p) orbitals and stretching the O–H bond to lower the adsorption energy, leading to the sensitivity enhancement of the nanoplates. These findings will be useful for the fabrication of metal oxide nanostructures with specifically exposed crystal surfaces for improved gas-sensing and/or catalytic performance.